Formulation and in vitro Evaluation of a Cosmetic Emulsion Containing Apple Juice Extract - Akhtar, Naveed; Muhammad Shoaib Khan, Haji; Rasool, Fatima; Ahmad, Mehmood; Saeed, Tariq (Asian Journal of Chemistry, 2010)
The aim of this study is to prepare a stable water and oil emulsion (w/o) from the extract (3 %) of Malus domestica containing high percentage of antioxidant activity. Antioxidants has been widely used in the formulation of skin care product for human health. Due to its effects on collagen biosynthesis, it is considered as moisturizing and anti-aging active ingredient. In this study different solvents were used for the extraction of flavonoids from fruit. Formulation, preparation techniques and in vitro characterization methods of emulsions were observed. Different solvents were used and it was found that methanol: formic acid:water (MFW, 70:2:28) is the best for recovery of flavonoids (antioxidant) from fruit. Stability studies of this emulsion were carried out at different storage conditions i.e., 8 ºC (in refrigerator), 25 ºC (in oven), 40 ºC (in oven) and 40 ºC + 75 % relative humidity (RH) (in stability cabin) for 28 days. Different parameters like pH, electrical conductivity and effect of centrifugation (simulating gravity) were determined during stability studies. Date obtained was evaluated stastistically using ANOVA two way analysis and LSD test. No phase separation was observed in sample during stable studies. It was found that both, the base and the formulation, were stable at all the accelerated conditions. Significant changes in the pH of base while insignificant changes in the pH of formulation were observed with the passage of time.